Vitamin C and E can alleviate negative effects of heat stress in Japanese quails - Şahin, Kazım; Şahin, Nurhan; Onderci, Muhittin; Gursu, Mehmet F.; Issi, Mustafa (Wfl Publ, 2003)
The present study investigates the effects of vitamin C (L-ascorbic acid) and E (alpha-tocopherol acetate) supplementation on egg production, egg quality, apparent digestibility, serum metabolites, and antioxidant status of Japanese quails (Coturnix coturnix japonica) exposed to a high ambient temperature (33 degrees C). One hundred and twenty laying Japanese quails (45-d-old) were divided into four groups, 30 birds per group. Quails were fed a basal diet or the basal diet supplemented with either 250 mg of L-ascorbic acid/kg of diet, 250 mg of alpha-tocopherol-acetate/kg of diet, or 250 mg of L-ascorbic acid plus 250 mg alpha-tocopherol-acetate/kg of diet. Separately or as a combination, supplemental vitamin C and E significantly increased live weight, feed intake and egg production (P < 0.05). Separately, dietary supplementation of vitamin C and E improved the egg quality, and the combination of vitamins C and E resulted in a greatest egg weight, specific gravity and Haugh unit value, thickest egg shell, and heaviest egg shell weight (P < 0.05). Apparent digestibility of nutrients (DM, OM, CP, and EE) was increased by supplementation of vitamin C and E (P < 0.05). Separately or as a combination, supplemental vitamin C and E increased serum concentration of total protein but decreased corticosterone, glucose, and cholesterol concentrations (P < 0.05). Supplemental vitamin C and E also increased serum vitamin C and E but decreased MDA (malondialdehyde) concentrations (P < 0.05). Results of the present study show that dietary supplementation of vitamin C and E, particularly as a combination, improved the performance, egg quality and antioxidant status of laying Japanese quails exposed to heat stress. Such a combination of supplement can offer a potential protective management practice in preventing heat stress-related losses in performance of laying Japanese quails.
Keywords: Heat stress; vitamin C; vitamin E; egg; digestibility; MDA; quail